1988
DOI: 10.1063/1.341253
|View full text |Cite
|
Sign up to set email alerts
|

Heavily Si-doped GaAs grown by metalorganic chemical vapor deposition

Abstract: Heavily Si-doped GaAs layers were grown by a metalorganic chemical vapor deposition method using disilane (Si2H6) as a silicon dopant source gas. The grown layers were characterized by the van der Pauw, secondary ion mass spectroscopy, and low-temperature Fourier transformation infrared spectroscopy (FTIR) method. The carrier concentration has no growth temperature dependence from 550 to 700 °C temperature range. However, it has temperature dependence below 550 °C and above 700 °C. The carrier concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…When using pure DTBSi (100 %), the electron concentration decreases down to 7.4×10 18 cm −3 . We attribute this drop to the self-compensation caused by the formation of Si V complexes [23] or even Si due to its amphoteric character [1]. Finally, as pointed out in the experimental section, we stress here the necessity of using an elevated temperature for the DTBSi cell in order to achieve a high doping efficiency.…”
Section: Gaas Doping Using H 2 -Diluted Dtbsimentioning
confidence: 68%
See 2 more Smart Citations
“…When using pure DTBSi (100 %), the electron concentration decreases down to 7.4×10 18 cm −3 . We attribute this drop to the self-compensation caused by the formation of Si V complexes [23] or even Si due to its amphoteric character [1]. Finally, as pointed out in the experimental section, we stress here the necessity of using an elevated temperature for the DTBSi cell in order to achieve a high doping efficiency.…”
Section: Gaas Doping Using H 2 -Diluted Dtbsimentioning
confidence: 68%
“…These values are comparable to those reported in Refs. [1,8,26,27] for GaAs layers doped with Si using different precursors including DTBSi. We thus conclude that the dilution of DTBSi in H 2 for the n-type doping of GaAs has no impact on the electron mobility.…”
Section: Gaas Doping Using H 2 -Diluted Dtbsimentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations carried out on Sidoping of GaAs showed that the dissociation of SiH 4 strongly increases in the range between 690°C and 770°C and thus a higher incorporation of Si into the lattice is expected at higher temperatures. 7,8 This could explain the existence of the band-tails in sample D. In addition the samples A through D show a decreasing blue-shift of the peak with increasing excitation indicating a better screening of the piezoelectric field F PE in the higher doped samples (compare solid and dotted curves in Fig. 1).…”
Section: Growth Of Samplesmentioning
confidence: 87%
“…, the generation of a compensating center related to the incorporation of carbon [Chichibu92], the formation of complexes or precipitates [Furuhata88],…”
Section: Heavily Si-doped Gaas Growthmentioning
confidence: 99%